Plesionika narval Fabricius 1787 - Li, Xinzheng (Zenodo, 2006)
Plesionika narval (Fabricius, 1787) Astacus Narval Fabricius, 1787: 331 [type locality: probably Nice, Mediterranean]. Plesionika narval – Lemaitre & Gore, 1988: 385, Fig. 3 k-m, 4; Chan & Crosnier, 1991: 443, Figs. 12a-c, 13a, 14a-c, 15a-e, 34-36; Li & Komai, 2003: 265. Material examined. – 2 males, 2 females, CN 6-1, South China Sea, 18 ° 30'N 110 ° 30'E, 112 m, sandy mud, AT, coll. Jixing Liu, 27 Jan.1959; 1 male, CN K66 B-47, South China Sea, 20 ° 00'N 113 ° 00'E, 117 m, muddy sand, AT, coll. Xiutong Ma, 11 Jul.1959; 1 juvenile, CN N138 B-21B, South China Sea, 18 ° 30'N 110 ° 15'E, 51.3 m, soft mud, BT, coll. Shoupeng Shen, 9 Mar.1960; 5 males, 9 ovigerous females, CN SSBIII17-57, Nansha Islands, 6 ° 29.50'N 108 ° 15.77'E, 94 m, muddy sand, AT, 7 May.1986; 1 ovigerous female, CN SSIVB46-33, Nansha Islands, 4 ° 00.00'N 109 ° 59.70'E, 99 m, muddy sand, AT, 15 May.1987; 1 male, 1 female, CN 8, Nansha Islands, 5º19.68'N 112º05.54'E, 127 m, muddy sand, AT, coll. Zhican Tang, 31 Jul.1988; 1 ovigerous female, CN 90 C-0116B, Qinglan, Hainan Island, trawling, 5 Nov.1990; 50 ex., CN 93 NS12-1, Nansha Islands, no detailed locality data, 107 m, fishing net, coll. Shaowu Wang, 2 May.1993; 3 males, 2 ovigerous females, CN 93 NS17-2, Nansha Islands, Nansha Islands, no detailed locality data, 106 m, fishing net, coll. Shaowu Wang, 4 May.1993; 1 male, CN CJ97 C-433, Sanya fishing harbor, Hainan Island, coll. Xinzheng Li, 28 Nov.1997. Distribution . – Mediterranean, eastern Atlantic from Gibraltar to Cape Verde Islands, South Atlantic, Red Sea, Indo-West Pacific from Madagascar to French Polynesia and northward to Japan, at depths of 35- 400 m. Remarks. – Not previously reported from the Nansha Islands. : Published as part of Li, Xinzheng, 2006, Additional Pandaloid Shrimps From The South China Sea (Crustacea: Decapoda: Caridea), With Description Of One New Species, pp. 361-372 in Raffles Bulletin of Zoology 54 (2) on page 370, DOI: 10.5281/zenodo.4508022 : {"references": ["Fabricius, J. C., 1787. Mantissa Insectorum sistens eorum Species nuper detectas adjectis Characteribus genericis, Differentiis specificis, Emendationibus, Observationibus. Vol. 1, 348 pp. Hafniae: Christ. Gottl. Proft."]}